1978
DOI: 10.1159/000232011
|View full text |Cite
|
Sign up to set email alerts
|

Specific Antibodies in Infants with Gastrointestinal Intolerance to Cow’s Milk Protein

Abstract: Antibodies of various immunoglobulin classes against cow’s milk proteins were studied in infants and children with cow’s milk protein intolerance, gluten-sensitive enteropathy and acute gastroenteritis. Their IgE, IgG, IgM and IgA antibody levels determined with the enzyme-linked immunosorbent assay (ELISA) and the IgE antibodies also determined with RAST, were compared with reference groups of children and adults. IgE, IgG or IgA antibodies against unseparated cow’s milk proteins, α-lactalbumin, β-lactoglobul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
2

Year Published

1980
1980
2003
2003

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 18 publications
2
33
2
Order By: Relevance
“…While the low numbers of late reactors in this study preclude definitive statisti cal analysis of antibody levels, it is of interest that the 3 patients who showed the highest levels of IgE milk antibodies for this group developed eczema after milk challenge. Our observation that elevated IgE antibod ies may appear in immediate and late forms of CMA suggests that Dannaeus and Johansson [2], who dem onstrated immediate skin reactions in acute CMA, and Fallstrom [9], who found elevated total IgE levels in late-onset CMA, were merely studying different aspects of the spectrum of milk allergy in childhood. A type 1 hypersensitivity response alone cannot ex plain the slow onset of clinical reaction in these latereacting patients.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…While the low numbers of late reactors in this study preclude definitive statisti cal analysis of antibody levels, it is of interest that the 3 patients who showed the highest levels of IgE milk antibodies for this group developed eczema after milk challenge. Our observation that elevated IgE antibod ies may appear in immediate and late forms of CMA suggests that Dannaeus and Johansson [2], who dem onstrated immediate skin reactions in acute CMA, and Fallstrom [9], who found elevated total IgE levels in late-onset CMA, were merely studying different aspects of the spectrum of milk allergy in childhood. A type 1 hypersensitivity response alone cannot ex plain the slow onset of clinical reaction in these latereacting patients.…”
Section: Discussionmentioning
confidence: 95%
“…Like Savilahti [3] and Fallstrom et al [9] we have identified a third group of late-reacting CMA patients who developed mainly gastrointestinal symptoms and/or eczematous lesions more than 20 h after com mencing milk ingestion [5]. While the low numbers of late reactors in this study preclude definitive statisti cal analysis of antibody levels, it is of interest that the 3 patients who showed the highest levels of IgE milk antibodies for this group developed eczema after milk challenge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, later studies have not verified such changes in complement: no reduction in C3 took place during nine challenges in CMA with malabsorption (98); and in three other series with 43 similar positive challenges with CM the complement fractions measured were unchanged (28,79,116). In 13 children with AD and CMA complement fractions 3 and 4 were unchanged during the positive challenge test (86).…”
Section: Serum Complement Fractionsmentioning
confidence: 99%
“…coeliac disease [5,6], cow's milk protein intolerance of delayed onset [7,8] and inflammatory bowel disease [9,10]. T cells are held to play a central role in these conditions.…”
Section: Introductionmentioning
confidence: 99%